Alterations of gut microbes and their correlation with clinical features in middle and end-stages chronic kidney disease - Chen, Hao; Wang, Jingyan; Ouyang, Qin; Peng, Xinyue; Yu, Zheng; Wang, Jianwen; Huang, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
Gut microecosystem has been shown to play an important role in human health. In recent years, the concept of the gut-kidney axis has been proposed to explain the potential association between gut microbiota and chronic kidney disease (CKD). Here, a cohort of fecal samples collected from patients with CKD (n = 13) were involved. The composition of gut microbial communities and clinical indicators in CKD and end-stage renal disease (ESRD) were characterized. Our study focused on the changes in gut microbiome and the correlation with clinical features in patients with CKD and ESRD by analyzing high-throughput sequencing results of collected feces. We elucidated the alterations of gut microbiota in CKD patients at different stages of disease and initially identified the gut microbiota associated with CKD progression. We also combined correlation analysis to identify clinical features closely related to the gut microbiome. Our results offer the possibility of using non-invasive gut microbiome in the early diagnosis of course from CKD to ESRD and provide new insights into the association between clinical indicators and gut microbiota in CKD.